2017
DOI: 10.4132/jptm.2016.11.03
|View full text |Cite
|
Sign up to set email alerts
|

GLUT1 as a Prognostic Factor for Classical Hodgkin’s Lymphoma: Correlation with PD-L1 and PD-L2 Expression

Abstract: BackgroundGlucose transporter type 1 (GLUT1) expression is linked to glucose metabolism and tissue hypoxia. A recent study reported that GLUT1 was significantly associated with programmed death ligand 1 (PD-L1) as a therapeutic target in relapsed or refractory classical Hodgkin’s lymphoma (cHL). The purpose of this study was to measure the expression of GLUT1 and assess its prognostic significance and potential relationships with PD-L1, programmed death ligand 2 (PD-L2), and programmed death-1 (PD-1) expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 37 publications
(48 reference statements)
1
18
0
Order By: Relevance
“…Pin wu et al performed a meta-analysis of solid tumors and showed that PD-L1 overexpression was associated with poor 3-year OS in all studies analyzed, with the exception of one study on melanoma and lung cancer. Interestingly, few studies of the PD-1 and PD-L1 pathway in HL have been performed [47] , [48] . HL usually exhibits diffuse and strong PD-L1 positivity in tumor (RS) cells based on IHC [49] .…”
Section: Discussionmentioning
confidence: 99%
“…Pin wu et al performed a meta-analysis of solid tumors and showed that PD-L1 overexpression was associated with poor 3-year OS in all studies analyzed, with the exception of one study on melanoma and lung cancer. Interestingly, few studies of the PD-1 and PD-L1 pathway in HL have been performed [47] , [48] . HL usually exhibits diffuse and strong PD-L1 positivity in tumor (RS) cells based on IHC [49] .…”
Section: Discussionmentioning
confidence: 99%
“…The presence of hypoxia-response elements (HRE) within the PD-L1 promoter region has highlighted a therapeutically attractive link between hypoxia/angiogenesis and anti-tumor immune suppression, 26 with similar mechanisms being implied in the regulation of PD-L2 expression. 27 …”
Section: Discussionmentioning
confidence: 99%
“…Biologically, elevated PD-L1 expression within tumor cells or the surrounding microenvironment is dynamic as a result of various molecular events including hypoxia 17 and similar correlations have been highlighted for PD-L2. 18 We have previously shown that activation of hypoxia inducible factor 1α (Hif-1α) is a key molecular hallmark in the metastatic progression of PCC/PGL, 19 a disease where constitutive Hif-1α stabilization secondary to mitochondrial dysfunction, termed “pseudo-hypoxia,” is a key pathophysiological trait. 20 …”
Section: Introductionmentioning
confidence: 99%
“…20,21 As mentioned above, it has been reported that the PD-L1 expression is positively regulated by HIF-1A activation and that HIF-1A-induced GLUT1 expression is related to high PD-L1 expression and EMT induction, which is characterised by E-cadherin suppression and cancer aggressiveness. 42,43 Conversely, PD-L1 expression has been reported to be downregulated by EMT induction, and the high 18 F-FDG-uptake in cancer tissues is negatively related to low E-cadherin expression as one of the EMT phenotypes. 23 Interestingly, the HIF-1A/GLUT1/ EMT axis has been known to regulate PD-L1 expression as well as 18 F-FDG-uptake; 22,28 however, the relationship between PD-L1 expression, FDG-uptake, and the HIF-1A/GLUT1/EMT axis in identical OSCC samples has not yet been investigated.…”
Section: Discussionmentioning
confidence: 99%